Efektivitas Aplikasi Wordwall pada Materi Statistika di SMKN 1 Jabon - Solichuddin, Mohammad; Dhewy, Risdiana Chandra; Sukriyah, Dewi (Mathematical Sciences and Applications Journal, 2024)
Along with the advancement of technology, digital-based learning media are increasingly used in the educational process. One of the learning media that can be utilized is the Wordwall application. This study aims to assess the effectiveness of using the Wordwall application in teaching Statistics at Vocational High School 1 Jabon. The Wordwall application was used as an interactive tool to motivate students and enhance their understanding of the subject matter. This research employed a descriptive quantitative method, involving 11th-grade students of the Creative Batik and Textile Crafts class 1 as the research sample. The instruments used included teacher ability observation sheets, student activity observation sheets, learning outcome tests, and student response questionnaires. The results showed that the teacher's ability to manage learning using Wordwall was categorized as very good, student activities were highly active, and student learning mastery reached 91%. Additionally, students' responses to the use of Wordwall were generally positive, with a percentage of  \(>=\)70%. Based on these findings, it can be concluded that the use of the Wordwall application is effective in improving students' understanding and motivation in learning Statistics.